2021
DOI: 10.1371/journal.pone.0250814
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation and factors associated with unsafe child stool disposal in Ethiopia: A spatial and multilevel analysis

Abstract: Background Unsafe disposal of children’s stool makes children susceptible to fecal-oral diseases and children remain vulnerable till the stools of all children are disposed of safely. There is a paucity of data on spatial distribution and factors associated with unsafe child stool disposal in Ethiopia. Previous estimates, however, do not include information regarding individual and community-level factors associated with unsafe child stool disposal. Hence, the current study aimed (i) to explore the spatial dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
(48 reference statements)
6
4
0
Order By: Relevance
“…The odds of safe stool disposal increases with increasing child age. This is finding is consistent with the studies done in Malawi, Ethiopia, Eswatini and Ghana [ 17 , 20 , 26 , 30 ]. The possible reason might be that as children get older especially starting from 6 months as they start complementary feeding their stool becomes offensive which increases the likelihood of safe stool disposal in older children as compared to younger children less than 6 month whose stool is not offensive making it favorable to defecate on clothes/diapers.…”
Section: Discussionsupporting
confidence: 93%
“…The odds of safe stool disposal increases with increasing child age. This is finding is consistent with the studies done in Malawi, Ethiopia, Eswatini and Ghana [ 17 , 20 , 26 , 30 ]. The possible reason might be that as children get older especially starting from 6 months as they start complementary feeding their stool becomes offensive which increases the likelihood of safe stool disposal in older children as compared to younger children less than 6 month whose stool is not offensive making it favorable to defecate on clothes/diapers.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with earlier studies in Ethiopia 51 and Cambodia, 50 geographic variation in stool disposal practices was observed in which the odds of hygienic stool practice increased in the Eastern and Southern Regions when compared to women in the West. A possible explanation for the observed geographic variation in stool disposal practice might be differences in the availability of toilet and water facilities, as well as policies guiding sanitation in the sub-regions.…”
Section: Discussionsupporting
confidence: 89%
“…The study revealed that women from households with unimproved toilet and water facilities were less likely to practice hygienic stool disposal compared to those with improved toilet and water facilities consistent with previous studies. 44,51,52 Compared to those living in homes that rely on public restrooms, people in low-income urban households having access to within-compound toilet facilities are more likely to utilise latrines for child defecation and stool disposal. 53 Stool disposal practices seem to improve with the availability of water resources on the compound.…”
Section: Discussionmentioning
confidence: 99%
“…The odds of safe stool disposal increases with increasing child age. This is nding is consistent with the studies done in Malawi, Ethiopia, Eswatini and Ghana (15,18,25,29) .The possible reason might be that as children get older especially starting from 6 months as they start complementary feeding their stool becomes offensive which increases the likelihood of safe stool disposal in older children as compared to younger children less than 6 month whose stool is not offensive making it favorable to defecate on clothes/diapers.…”
Section: Discussionsupporting
confidence: 89%